TRENDS AND PATTERNS OF SELF EFFICACY IN ATHLETE: BIBLIOMETRIC ANALYSIS FROM 2014-2024 - Adityaputra, Amran Hasbi; Dini Rahma Bintari (Gladi : Jurnal Ilmu Keolahragaan, 2024)
This study aims to map the development of scientific research on self-efficacy in athletes from 2014 to 2024 using bibliometric analysis. Data was collected from the Scopus database, and the study analyzed trends in publication, collaboration between researchers, and the most frequently occurring keywords. The findings show a significant increase in the number of articles, especially in recent years, with key themes such as mental health, athletic performance, and sports injuries being frequently explored. Future research is recommended to focus more on the psychological aspects of athlete rehabilitation and the development of technology-based intervention programs to enhance self-efficacy.